Association between the Munich Chronotype Questionnaire and Wrist Actigraphy. (9th May 2018) - Santisteban, Jose Arturo; Brown, Thomas G.; Gruber, Reut
Abstract : Chronotype refers to individuals' preferences for timing of sleep and wakefulness. It can be quantified by measuring the midpoint time between the start and end of sleep during free days. Measuring chronotype is helpful to diagnose circadian rhythm sleep-wake disorders. The Munich Chronotype Questionnaire (MCTQ) is a self-reported measure of chronotype that calculates the midpoint of sleep on free days based on self-reported bed and wake times. Self-reports of sleep are prone to bias. The objective was to examine the agreement between the MCTQ-derived midpoint and an objective measure obtained using wrist actigraphy. The sleep of 115 participants aged 18–34 (mean = 24, SD = 4.6) was monitored with actigraphy for 4 to 6 consecutive nights. The corrected midpoint of sleep on free days was derived from sleep start and end times on both free days and scheduled days. The corrected midpoint of sleep on free days as measured by the MCTQ was 4:56 (SD = 1 : 16) and by actigraphy was 4:51 (SD = 1 : 23). They were not significantly different (t ( 87 ) = 0.66, p = 0.51 ). A strong correlation was found between these two measurements (r ( 88 ) = 0.73, p < 0.001 ) . The 95% limits of agreement were between −1:37:19 and 2:14:38. MCTQ and actigraphy provide similar results for the corrected midpoint of sleep on free days.